Association between restless legs syndrome and migraine. Issue 5 (30th November 2009) - Chen, Ping-Kun; Fuh, Jong-Ling; Chen, Shih-Pin; Wang, Shuu-Jiun
Abstract : Background: An association between restless legs syndrome and migraine has been reported recently. The clinical correlates and impact of comorbidity of restless legs syndrome (RLS) are not fully described in patients with migraine. Objectives: To investigate the frequency of RLS among different primary headache disorders, and its impact and clinical correlates in migraine patients. Methods: Consecutive patients with migraine, tension-type headache (TTH) and cluster headache (CH) were recruited in a headache clinic. Each patient completed the Migraine Disability Assessment (MIDAS) questionnaire, Hospital Anxiety and Depression Scale (HADS), Pittsburgh Sleep Quality Index (PSQI) and International RLS Study Group (IRLSSG) Rating Scale. RLS was diagnosed using the IRLSSG criteria. Results: A total of 1041 patients (migraine 772, TTH 218, CH 51) completed the study. The frequencies of RLS in patients with migraine (11.4%) was higher than in those with TTH (4.6%) or CH (2.0%) (p=0.002). In migraine patients, comorbidity with RLS was associated with higher frequencies of photophobia, phonophobia, exacerbation due to physical activities, vertigo, dizziness, tinnitus and neck pain, and higher mean scores of MIDAS and HADS. Migraine patients with RLS had a poorer sleep quality (Pittsburgh Sleep Quality Index score 11.1±4.1 vs 8.9±4.0, p<0.001) than those without. Conclusion: An association between migraine and RLS among different primary headache disorders is demonstrated. Comorbid RLS in migraine patients worsened sleep quality. A shared underlying mechanism may account for the correlates between migraine features and comorbid RLS.